Prevalência de alterações clínicas e espirométricas em indivíduos expostos à inalação de fumaça durante incêndio em casa noturna - Lidtke, Grazielli dos Santos (2015)
Smoke inhalation during home or commercial fire resulting in injury of the lung parenchyma and the upper airway by inhalation of toxic gases and products from incomplete combustion, occurring commitment by direct thermal injury and metabolic impairment. Death most often is caused by hypoxemia due to carbon monoxide inhalation and / or cyanide. Are independent predictors of mortality in burned patients: inhalation injury, older than 60 years and burned surface area greater than 40%, the presence of a single factor determines mortality of 3%, two factors 33% and 90% three factors. Inhalation of smoke determines airway edema by direct thermal injury, bronchospasm by irritating aerosolized and occlusion of the small airway by deposit debris endobronchial. Airway obstruction and bronchospasm manifest themselves within 24 hours. Chronic sequelae in victims of inhalation injury are rare. Pulmonary function tests are part of the assessment of victims of inhalation injury, most of them routine spirometry. On January 27, 2013 a nightclub in the city of Santa Maria / RS was the target of a major fire, which exposed many young people to inhalation of toxic fumes in a closed environment. At the time 242 young people died and many were injured mostly with inhalation injury. This study aims to evaluate which the prevalence of spirometric changes in individuals exposed to smoke inhalation, if there was a correlation between the type of manipulation of the airway and lung function and what were the initial symptoms. A cross-sectional study that included symptomatic patients referred to the Department of Pulmonology and who underwent pulmonary function tests in the first five months after exposure to the smoke of the fire. As a result, we obtained total of 125 individuals, symptoms after inhaling toxic fumes, these only nine had spirometric changes and there was no correlation between the type of intervention in the airway and lung function of the victims. Cough and dyspnea were the most prevalent symptoms soon after exposure. Cough and dyspnea were the most prevalent symptoms soon after exposure. Thus, we can infer that chronic pulmonary sequelae after smoke inhalation alone is a complication offbeat, but no significant effects on the flow and volume of pulmonary gases.